P10 Miliary tuberculosis: a retrospective review of cases presenting to a UK teaching hospital. (11th November 2022) - Molloy, H; Noonan, R; Gorsuch, T; Brij, SO
Abstract : Background: Miliary tuberculosis (TB) is one of the severest forms of TB and accounts for only 4% of all cases of TB in the UK. Despite effective treatment it continues to have a high mortality rate which is likely to be a consequence of the dissemination of Mycobacterium tuberculosis bacilli via the lymph and blood to the tissues. Aim: To review the epidemiology, management and outcome of all cases of miliary TB diagnosed in our population since 2005. Methods: A retrospective review of all of the cases of miliary TB diagnosed and treated locally between 2005 and 2021 was undertaken. Results: 38 cases miliary TB were identified: (male gender 71%; median age 36 years (IQR 28–53); non-UK born 95% and 75% diagnosed within 10 years of arrival in the UK). One patient was co-infected with HIV. The most common symptoms at presentation were cough (50%), weight loss (39%) and sweats (52%). Miliary shadowing on chest x-ray and/or CT scan present 78%. Multiple sites (mean 1.7; mode 2; range 0–4) were sampled in order to obtain microbiological confirmation ( figure 1 ). Majority (36; 95%) had sputum or lavage samples of which 15 (42%) culture positive. Overall, culture positivity was 66%. Cerebrospinal fluid sampling was undertaken in 18/38 (47%) to assess CNS involvement (lymphocytosis) although only 1 case cultured TB. Likewise, there was no culture positivity identified in early morning urine samples. 2 cases each of Isoniazid and Pyrazinamde resistance and 1 case MDR-TB were identified. 36 patients were treated successfully for the intended duration of therapy. Extended therapy (>6 months) in 20, the commonest reasons being CNS involvement (7), drug resistance (5) and disease severity (3). Conclusion: Miliary TB continues to be a rare condition and is associated with significant mortality. If persons do not have pulmonary involvement it may be difficult to obtain microbiological confirmation of infection. CSF sampling is good for exclusion of CNS TB but poor for obtaining culture and sensitivity to guide treatment.